Determinants affecting job performance among selected MITI agencies - Ahmad Barakbah, Asyraf (2020)
The purpose of this study to identify the determinants affecting job performance among selected MITI agencies. The research is based on sample of 85 respondents. The results show that self-motivation and social skill have significance influence of affecting job performance among selected MITI agencies. This study involves overall process of conducting research such as determining the sample, reliability and validity of questionnaire, research design, sampling technique, data collection method. Ministry of International Trade and Industry (MITI) have 11 agencies under them including Malaysia External Trade Development and Corporation (MATRADE), Malaysia Productvity Corporation (MPC), Malaysia Investment Development (MIDA) and etc. However, there are only two agencies have been picked which is MATRADE and MPC. The main objective in this study to identify whether self-regulation, self-awareness, self-motivation and social skill affect job performance among selected MITI agencies. The strongest relationship is between self-motivation and job performance among selected MITI agencies.